PHYSICO-CHEMICAL AND COMMERCIAL PROPERTIES OF MAGNESIUM-CONTAINING LIME AMMONIA NITRETTE - Nabiyev Abduraxim Abduxamidovich; Yunusova Go'zal; Tukhtamushova Anisa Ubayevna (International Journal on Orange Technologies, 2023)
In this work, we studied the physico-chemical and commercial properties of magnesium-containing lime ammonium nitrate (magnesium-containing IAS) (hygroscopic point, sorption kinetics of water vapor, sorption moisture capacity, dissolution rate, caking, porosity and bulk density of granules) were determined for fertilizer samples.